2019
DOI: 10.1007/s00374-019-01366-7
|View full text |Cite
|
Sign up to set email alerts
|

N2O emission increases with mulch mass in a fertilized sugarcane cropping system

Abstract: The nitrous oxide (N 2 O) emitted from soil was monitored to investigate the effect of sugarcane straw removal on the mechanisms that make mulch a Bhot spot^of N 2 O emissions under subtropical conditions. We conducted a field experiment with the firstratoon sugarcane with four amounts of straw (0, 4, 8, and 12 Mg ha −1) at the soil surface combined with 0 or 100 kg urea-N ha −1. The urea-N was applied 52 days after straw application. Over the course of 1 year, we measured the N 2 O and carbon dioxide (CO 2) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Thus, improved management of fertiliser applications could result in GHG emission mitigation through reduced N2O emissions. Some activities include split application of nitrogen fertiliser in combination with low irrigation, reduction in fertiliser application rates, substitution of nitrate-based fertiliser for urea (Rashti et al, 2015), removing mulch layer before fertiliser application (Pinheiro et al, 2019;Xu et al, 2019) or conversion of sugarcane to wetlands.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, improved management of fertiliser applications could result in GHG emission mitigation through reduced N2O emissions. Some activities include split application of nitrogen fertiliser in combination with low irrigation, reduction in fertiliser application rates, substitution of nitrate-based fertiliser for urea (Rashti et al, 2015), removing mulch layer before fertiliser application (Pinheiro et al, 2019;Xu et al, 2019) or conversion of sugarcane to wetlands.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we concluded that organic matter amendment can mitigate N 2 O emissions in soils with low NO 3 − content (due to higher N 2 O reduction), or trigger N 2 O fluxes when coupled with high soil NO 3 − content under the moist situation. Earlier studies reported that straw amendment has the potential to mitigate N 2 O emissions (Yao et al., 2017; Zou et al., 2005), while others showed that straw returning can increase N 2 O losses (Pinheiro et al., 2019; Wu et al., 2018). In this context, we believe that our study contributes to the understanding of why contradictory observations on the impact of straw addition on N 2 O fluxes have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that soil temperature and moisture can explain up to 86% variations of N 2 O emissions [39]. Soil N 2 O emissions varied with soil temperature in specific ranges [28,40], which may relate to different optimum temperatures of N-transforming microorganisms with or without N fertilization and different soil types [37,41]. Compared with soil temperature, soil moisture is the main factor impacting soil N 2 O emissions.…”
Section: Nitrogen Fertilization Stimulated Soil N 2 O Emissionsmentioning
confidence: 99%